The Effects of Noise on Aquatic Life - Popper, Arthur N.; Hawkins, Anthony (Advances in Experimental Medicine and Biology, 2012)
The Second International Conference on the Effects of Noise on Aquatic Life will take place in Ireland August 15-20, 2010. The main emphasis of the conference will be on defining the current state of knowledge. However, we will also assess progress in the three years since the First conference. The Second conference will place strong emphasis on recent research results, the sharing of ideas, discussion of experimental approaches, and analysis of regulatory issues.